Synthesis of curcumin derivatives containing non-steroidal anti-inflammatory drugs - Katarzyna Sowa-Kasprzak; Dorota Olender; Jacek Kujawski; Lucjusz Zaprutko; Anna Pawełczyk (Polskie Towarzystwo Farmaceutyczne, 2023)
Synthesis and biological evaluation of hybrid molecules combining naturally occurring antioxidant active structures with anti-inflammatory agents has been a strong trend in medicinal chemistry. This study focuses on modulating the structure of curcumin derivatives or their analogues with the use of non-steroidal anti-inflammatory drugs (NSAIDs). The combinations of curcumin, its keto-blocked derivatives and monocarbonyl analogues with selected non-steroidal anti-inflammatory drugs (ibuprofen, naproxen) were obtained and characterized. The pyrazole, isoxazole, benzylidene derivatives as well as curcumin monocarbonyl analogues were used as substrates in the reactions with selected NSAIDs. As a result of the esterification of curcumin-type diphenol, the corresponding mono- and diester-type derivatives were also obtained and characterized. Moreover, the estimated values of binding affinities and the binding sites of docked derivatives were deduced from modeling studies were very favorable. Results obtained show the binding potential of curcumin and its analogs to the host-targeted proteins nucleocapsid phosphoprotein (PDB ID: 6VYO) structure. Additionally, with the use of selected methods of computational chemistry (Molinspiration Cheminformatics and Osiris Property Explorer) the molecular parameters of the relevant molecules were calculated.